2013
DOI: 10.1074/jbc.m112.422287
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Unfolding of a Mammalian Pentameric Ligand-gated Ion Channel Proceeds at Consecutive, Distinct Steps*

Abstract: Background:The 5-hydroxytryptamine receptor (5-HT 3 R) is a prototypical pentameric ligand-gated ion channel. Results: The receptor's thermal stability was investigated in native plasma membranes, in detergent solution, and in reconstituted lipid bilayers. Conclusion: Unfolding of the 5-HT 3 R occurs via hierarchical, consecutive structural transitions, which can be distinguished experimentally. Significance: Our findings serve as an important base to create receptors of increased stability for structural/func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…Moreover, they highlight the heightened structural sensitivity of ELIC to its surrounding environment compared with GLIC, consistent with the hypothesis that intramembrane aromatic interactions enhance TMD stability. Previous studies have shown that TMD stability impacts the overall stability of a pLGIC (38).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they highlight the heightened structural sensitivity of ELIC to its surrounding environment compared with GLIC, consistent with the hypothesis that intramembrane aromatic interactions enhance TMD stability. Previous studies have shown that TMD stability impacts the overall stability of a pLGIC (38).…”
Section: Resultsmentioning
confidence: 99%
“…6d, inset) showed that after thermal unfolding, hisPS2 formed SDS-resistant aggregates that did not enter the separation gel. This kind of thermal unfolding-induced aggregation has also been reported for other membrane proteins [67,68].…”
Section: Thermal Stability Of the Secondary And Tertiary Structure Ofmentioning
confidence: 86%
“…Remarkable high melting temperatures could be observed, all of them were in the range of 60 to 80°C. The melting temperature of purified Alpo6-eGFP for example is 77 ± 1°C, not only exceeding the melting temperatures of eukaryotic members of the CLR family [27,35,53,57], but also clearly higher than the melting temperature of GLIC, a prokaryotic homologue with a T m of 52°C [58]. However, we have to consider the presence of eGFP in the intracellular loop.…”
Section: Discussionmentioning
confidence: 96%